2020
DOI: 10.1002/jso.26090
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of recurrence after total thyroidectomy plus neck dissection and radioactive iodine ablation for high‐risk papillary thyroid carcinoma

Abstract: Background American Thyroid Association (ATA) proposed management guidelines for differentiated thyroid cancer, including a three‐tiered risk stratification system for structural recurrence. This study aimed to compare the various 2015 ATA criteria for the strength of association with the recurrence of high‐risk papillary thyroid carcinoma (PTC). Study Design This study included 545 consecutive patients who underwent total thyroidectomy plus neck dissection and radioactive iodine ablation (RAI) for previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…We observed a significant influence of age on having an excellent response after initial therapy, developing NED, recurrence, and DSM for either PTC or FTC. Kim et al showed no influence of age on recurrence using 55 years age cutoff in patients with PTC (15); the recurrence rate in their patients was with 16.5% in line with ours (13.9%). On the other hand, Trimboli et al showed a significant influence of age on relapse using an age cutoff of 55 years of age in patients with high-risk DTC (14).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We observed a significant influence of age on having an excellent response after initial therapy, developing NED, recurrence, and DSM for either PTC or FTC. Kim et al showed no influence of age on recurrence using 55 years age cutoff in patients with PTC (15); the recurrence rate in their patients was with 16.5% in line with ours (13.9%). On the other hand, Trimboli et al showed a significant influence of age on relapse using an age cutoff of 55 years of age in patients with high-risk DTC (14).…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, the ATA Risk Stratification System may further improve should age be incorporated as an additional risk factor.American Joint Committee on Cancer (UICC/AJCC) Tumor, Node, Metastasis (TNM) staging system (11,12,13), age was not incorporated into the classification of patients into different prognostic groups. Recently, three studies investigated the influence of age on recurrence and disease outcome in patients with DTC (9,14,15), including those with ATA high-risk DTC. Subsequently, it was shown that the 2015 ATA Risk Stratification System…”
mentioning
confidence: 99%
“…A number of prognostic factors, including age, sex, histology, tumor size, vascular invasion, lymph node metastasis and extrathyroidal extension (ETE) have been identified as predictors of recurrence and patient outcome (16)(17)(18)(19)(20). However, there has been considerable controversy regarding microscopic ETE (m-ETE) (as determined histologically using microscopic evaluation) and its prognostic significance, as well as its association with recurrence (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies agree that LVI has a positive correlation with LNMs ( 19 22 ), and a negative impact on outcomes of patient ( 6 , 23 , 24 ), although single studies report no significant association with response to therapy ( 39 ). In this study, the positive correlation with LNMs can be confirmed.…”
Section: Discussionmentioning
confidence: 99%